Strategi Pemerintah Desa Dalam Pemberdayaan Masyarakat Miskin Di Desa Kelumu Tahun2024 (Studi Kasus Desa Kemulu Kabupaten Lingga 2024) - Nana Amelia Sefti; Ardi Putra; Khairi Rahmi (CV. ITTC INDONESIA, 2026)
Kelumu village Desil 1 has 84 KK/285 AK, Desil 2 has 64 KK/214 AK, Desil 3 has 53 KK/166 AK, and Desil 4 has 36 KK/88 AK. Then you can conclude that your village has a poverty rate of Desil 1 to 4 in the amount of 237 KK and 753 AK, thus it can be seen that your village has a poverty rate of 82.6% of 17.4% of the welfare rate. The problem is increasingly complex because the strategy of empowering poor people run by the village government has not been fully able to answer real challenges on the ground. The method used is qualitative decriptive. The seal in this study is the government of your elder village and the community of your elder village in 2024. Data collection techniques use observation, interview and documentation. Theories of data analysis use the theory of community empowerment planning to Bradfil (2021): program formulation, activity planning, program implementation, and evaluation. The results of this study show there is a link between the community and the village government and the activity of empowerment program in 2024, this is shown from the results of interviews and observations that empowerment in the village village is not maximal so that the village government still has to pay attention to the problem of poverty caused by low income and lack of community skills by providing employment training, business capital assistance, and opening up potential village-based employment opportunities so that the welfare of the community can increase.